Drug-related postural hypotension: to withdraw or not to withdraw (a case series) - Mohamad, Fadzilah; Devaraj, Navin Kumar; Abdul Rashid, Aneesa; Abdul Manap, Abdul Hadi (Consortium of Islamic Medical Colleges, 2019)
Orthostatic hypotension is a common presentation in the primary care setting. Concise management is important as it can lead to falls, particularly in the elderly and can lead to significant morbidity and mortality. Its management presents as a challenge as there are differing guidelines on managing these patients. This case report illustrates two cases of drug-related orthostatic hypotension with similar presentation, however both were managed differently.